Postictal Fugue in Temporal Lobe Epilepsy: A Case Report - Cindy Prianto; Edeline Samudra; Tiara Julianti; Retno Jayantri Ketaren (Universitas Pelita Harapan, 2025)
Introduction: Temporal lobe epilepsy (TLE) is the most prevalent form of epilepsy. Postictal fugue, a state of altered consciousness and amnesia that can lead to unusual behaviors, is an unusual type of postictal phase in TLE. This case report describes a rare case of postictal fugue in adult-onset TLE. Case Report: A 27-year-old man with complaints of recurrent seizures over the past six years, described as blank staring accompanied by purposeless action with each episode lasting 5-10 minutes on average. During the episodes, he can perform various activities without the ability to recall the events after regaining consciousness. There were neither aura nor specific triggers preceding the episodes. Some long-term memories are impaired. No other cognitive impairment is found. There was a long-standing history of substance use. Electroencephalogram examinations revealed abnormal spikes wave in bilateral temporal region. Discussion: The patient’s symptoms resemble dissociative fugue but is attributed to an organic etiology, which is mesial/limbic TLE. The postictal phase which manifests as postictal fugue is caused by the abnormal electrical activity in the hippocampus leading to disruption in memory formation and spatial navigation. The underlying mechanism causing epilepsy is thought to be related to the prolonged history of substance abuse. Conclusion: The postictal phase in TLE can present in various forms and may be challenging to diagnose. Therefore, it is crucial to thoroughly investigate the causes of organic dissociative disorder, including postictal fugue in TLE.